Indium and hafnium chloride modified titanium oxide thin films - Kuruoglu, Neslihan Ayarci; Choi, Fatma Pinar Gokdemir; Ozdemir, Orhan (ELSEVIER GMBH, 2023)
Titanium oxide (TiO2) thin films were prepared by the sol-gel spin-coating technique. The in-fluences of indium (In), hafnium (Hf), and In&Hf doping on electrochemical and structural properties were investigated. The structural properties of undoped and doped TiO2 were inves-tigated using thermogravimetric/differential thermal (TG/DTA), X-ray Powder Diffraction (XRD), and atomic force microscopy (AFM). The optical properties were investigated using ultra-violet-visible (UV-Vis) spectroscopy, and band gap energies were calculated using the Tauc method from transmission measurement. The results showed that TiO2 had better electrochemical properties, and the band gap increased with In&Hf doping.
Keywords: Metal ion doping; Indium; Hafnium; Titanium oxide; Cathodic electrochromic film; Sol -gel; DOPED TIO2 FILMS; PHOTOCATALYTIC ACTIVITY; ELECTROCHROMIC PROPERTIES; TEMPERATURE DEPOSITION; AMORPHOUS TIO2; ANATASE; PERFORMANCE; ELECTRODES; DIOXIDE; Optics